Covid-19 and disinformation as a global phenomenon: A view from fact-checking - Andrade Ferreira, Nuno (2022)
Covid-19 pandemic is the largest global health crisis faced by mankind in several decades. Alongside with public health, disinformation has emerged as an additional challenge. World Health Organization considers that we are facing an infodemic and warns about the polarization of the debate around SARS-CoV-2. Although it isn’t a recent phenomenon, nor is the concept fully defined, disinformation benefits from the development of information and communication technologies in order to expand and establish its global relevance, changing communication spaces. Fact-checking has gained space in the media field, achieving special relevance throughout 2020, as a specialized area of journalistic action and as a response to disinformation associated with the pandemic. In this article, we tried to find the global character of disinformation related to covid-19. We collected and analysed articles published by five media dedicated to fact-checking, located in Africa, North America, South America, Europe and Asia. The research identified the prevalence of topics covered by all or several media, with particular relevance to articles related to covid-19 vaccines. We also observed a dominance of social media as the main source of the analysed content.